2001
DOI: 10.1038/sj.bmt.1703155
|View full text |Cite
|
Sign up to set email alerts
|

High incidence of gastrointestinal tract bleeding after autologous stem cell transplant for primary systemic amyloidosis

Abstract: Summary:Peripheral blood stem cell transplants have been associated with better response rates than conventional chemotherapy in patients with primary systemic amyloidosis. A higher incidence of gastrointestinal (GI) tract bleeding has been observed among amyloidosis patients undergoing peripheral stem cell transplantation. We retrospectively reviewed the medical records of such patients to identify those who had GI tract bleeding in the post-transplant period. Forty-five patients were studied. Nine patients h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
23
1

Year Published

2003
2003
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(26 citation statements)
references
References 37 publications
2
23
1
Order By: Relevance
“…In AL, most patients are hematologically normal yet have significant organ dysfunction at the site of amyloid deposition: heart, liver, nerve, kidney, or lung. Patients may die of cardiac arrhythmias, 8 fatal pulmonary toxicity, 36 intractable cardiac failure, 7 gastrointestinal tract bleeding, 37 or precipitous renal failure, 15 which is rarely if ever seen in multiple myeloma. The decision to treat a patient with AL by transplantation must be undertaken with extreme caution, and ultimately a phase 3 trial to assess transplantation will be necessary, so the mistakes of transplantation for breast cancer are not repeated.…”
Section: Discussionmentioning
confidence: 99%
“…In AL, most patients are hematologically normal yet have significant organ dysfunction at the site of amyloid deposition: heart, liver, nerve, kidney, or lung. Patients may die of cardiac arrhythmias, 8 fatal pulmonary toxicity, 36 intractable cardiac failure, 7 gastrointestinal tract bleeding, 37 or precipitous renal failure, 15 which is rarely if ever seen in multiple myeloma. The decision to treat a patient with AL by transplantation must be undertaken with extreme caution, and ultimately a phase 3 trial to assess transplantation will be necessary, so the mistakes of transplantation for breast cancer are not repeated.…”
Section: Discussionmentioning
confidence: 99%
“…Localized or diffusely spread amyloid involvement of the submucosa, the muscularis mucosa, and subserosa, as well as the vasculature of the gastrointestinal (GI) tract, is frequently observed [9,22]. It is usually asymptomatic or associated with nonspecific symptoms, such as anorexia, nausea, diarrhea, abdominal pain, weight loss, or malabsorption [22] and pseudo-obstruction [3].…”
Section: Gastrointestinal Amyloidosismentioning
confidence: 99%
“…Hypercalcemia, dehydration, infection, nonsteroidal anti-inflammatory agents, and radiographic contrast media may contribute to renal failure. In more than half of the patients, renal function may recover within the first few months [22]. However, 18% of patients with AL amyloidosis require dialysis, which is associated with a median survival time of <1 year [23].…”
Section: Renal Involvementmentioning
confidence: 99%
See 1 more Smart Citation
“…Several reports have shownthat the rate of complete remission in the production of Mprotein reached around 60% or more (12,17). This therapy is, of course, more risky than other chemotherapeutic regimens in patients with amyloidosis-induced dysfunction in multiple vital organs (18,19). Recently, it has been reported that the performance status and degree of cardiac involvement are important as potentially fatal risk factors after high-dose melphalan with auto-PBSCTin patients with AL amyloidosis (20).…”
mentioning
confidence: 99%